Clinical features, biochemistry and HLA-DRB1 status in youth-onset type 1 diabetes in Pakistan. (March 2019) - Fawwad, Asher; Govender, Denira; Ahmedani, Mohammad Yakoob; Basit, Abdul; Lane, Julie Ann; Mack, Steven John; Atkinson, Mark Alvin; Henry Wasserfall, Clive; Ogle, Graham David; Noble, Janelle Annette
Abstract: Published information on diabetes in Pakistani youth is limited. We aimed to investigate the demographic, clinical, and biochemical features, and HLA-DRB1 alleles in new cases of diabetes affecting children and adolescents <22 years of age. The study was conducted at Baqai Institute of Diabetology and Endocrinology in Karachi from June 2013-December 2015. One hundred subjects aged <22 years at diagnosis were enrolled. Demographic characteristics, clinical information, biochemical parameters (blood glucose, HbA1c, C-peptide, glutamic acid decarboxylase 65 (GAD65) and islet antigen 2 (IA-2) autoantibodies) were measured. DNA from 100 subjects and 200 controls was extracted and genotyped for HLA-DRB1 using high-resolution genotyping technology. Ninety-nine subjects were clinically diagnosed as type 1 diabetes (T1D) and one as type 2 diabetes (T2D). Of the 99 with T1D, 57 (57.6%) were males and 42 (42.4%) females, with mean age at diagnosis 11.0 ± 5.2 years (range 1.6–21.7 years) and peaks at six and fifteen years. Fifty-seven subjects were assessed within one month of diagnosis and all within eleven months. For the subjects diagnosed as T1D, mean C-peptide was 0.63 ± 0.51 nmol/L (1.91 ± 1.53 ng/mL), with 16 (16.2%) IA2 positive, 53 (53.5%) GAD-65 positive, and 10 (10.1%) positive for both autoantibodies. In T1D patients, the allele DRB1*03:01 demonstrated highly significant T1D association (p < 10 −16 ), with no apparent risk conferred by DRB1*04:xx alleles. Conclusions: Heterogeneous forms of T1D appear more common in children and youth in Pakistan than in European populations. Individual understanding of such cases could enable improved management strategies and healthier outcomes.